Association of Genetic Variants at the 4q25 Locus with Atrial Fibrillation in Indian Population. Issue 1 (27th June 2016) - Bhanushali, Aparna; Nair, Akhil; Jagdale, Ganesh; Suvarna, Tilak; Das, Bibhu R.
Abstract : Introduction: Atrial fibrillation (AF) is the most common cardiac arrhythmia in clinical settings known to impair cardiac function. Genome‐wide association studies identified SNPs on chromosome 4q25 to be associated with AF. Till date no information is available from India related to the association of these variants with AF. Materials and Methods: Two hundred and sixty‐seven individuals comprising of 170 patients with Coronary Artery Disease (CAD), 41 patients with AF, and 56 healthy controls were genotyped for rs10033464 and rs2200733 at 4q25 locus. Results: Strong association of rs10033464 with AF was observed on comparison with control groups (OR: 2.59; 95% CI: 1.08–6.21; P : 0.031) and between post‐coronary artery bypass grafting (CABG) AF and control with dominant genetic model (OR: 4.73; 95% CI: 1.50–14.89; P : 0.0071). Comparison of post‐CABG AF with CAD also indicated association (OR: 2.73; 95% CI: 0.9–7.56; P value: 0.05). In contrast, the rs2200733 C>T variant did not show any association with post‐CABG AF, but with lone AF with the 'T' allele being associated with increased risk was seen (OR: 2.80; 95% CI: 1.08–7.24; P value: 0.042). Conclusion: In conclusion, the rs10033464 (T) allele is associated with the risk of post‐CABG AF and the rs2200733 (T) with lone AF.